Levels of oil residues in some coastal lagoons, East of Libya - Al-Asadi, M.K.K. (Mesopotamian Journal of Marine Sciences, 2022)
Four Coastal lagoons, namely Bomba, Katayta, Bardia and Um El-Shawish located in the eastern part of Libya investigated seasonally for oil pollution throughout the period from July 1998 to April 1999 at five stations. The lowest level of oil pollution was observed in summer while the highest level was observed in spring. There was an evidence of seasonal variation which is attributed to the environmental conditions prevailing in the specific ecosystem. Spectroflourometeric method have been adopted to measure the total concentration of petroleum hydrocarbons TPHs .Levels of TPHs ranged from 3.33 µg/l in summer to 27.91 µg/l in spring, in Bomba Gulf, in Katayta ranged, from 4.09 µg/l in summer to 27.09 µg/l in spring, from 3.50 µg/l in summer to 28.48 µg/l in spring in port Bardia, from 6.33 µg/l in autumn to 10.93 µg/l in winter, in Um El-Shawish Inlet. It was suggested that 10 µg/l indicate contamination of marine life with oil.